2004
DOI: 10.1007/s10549-004-0805-2
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of Stat5a in rat mammary gland carcinogenesis

Abstract: Signal transducer and activator of transcription (Stat) 5a is a transcription factor mediating the action of specific cytokines, growth factors and hormones on gene expression. In the mammary gland, Stat5a is well recognized for its function in prolactin signaling, lobuloalveolar development, and milk protein expression during pregnancy and lactation. Latent cytoplasmic Stat5a is activated by tyrosine phosphorylation and following dimerization undergoes nuclear import. In the current study, Stat5a expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…This has been reported in one study where 76% of the breast cancers examined showed phosphorylated STAT 5a to be present in the nucleus [8]. It has also been shown that in 65% of induced rat mammary gland tumors, STAT 5a was detected in the nucleus using phosphorylation-specific antibodies [23].…”
Section: Discussionmentioning
confidence: 60%
“…This has been reported in one study where 76% of the breast cancers examined showed phosphorylated STAT 5a to be present in the nucleus [8]. It has also been shown that in 65% of induced rat mammary gland tumors, STAT 5a was detected in the nucleus using phosphorylation-specific antibodies [23].…”
Section: Discussionmentioning
confidence: 60%
“…In the same study, a significant correlation between a high STAT5A nuclear expression and high tumour grade was observed. A significantly increased nuclear localisation of STAT5A has also been shown in human BCs (Cotarla et al 2004, Shan et al 2004.…”
Section: Introductionmentioning
confidence: 67%
“…Immunohistochemical approaches in humans have found increased levels of nuclear localised STAT3 in malignant BCs when compared with normal tissues (Clevenger 2004). Nuclear expression of STAT5A in chemically induced rat mammary gland cancers and preneoplastic lesions has been detected, when compared with cytosolic STAT5A expression in the control tissue (Shan et al 2004). In the same study, a significant correlation between a high STAT5A nuclear expression and high tumour grade was observed.…”
Section: Introductionmentioning
confidence: 99%
“…In a study using the rat mammary gland as a model, Shan et al (2004) examined the immunohistochemical expression and activation of STAT5A in a panel of rat mammary gland carcinomas induced by the chemical carcinogens, 7,12-dimethylbenz[a]anthracene and 2-amino-1-methyl-6 phenylimidazo [4,5-b]pyridine, to assess the percentage of cells in carcinomas and preneoplastic lesions showing tyrosine phosphorylated and nuclear localized STAT5A. Nuclear immunostaining of STAT5A was detected in 65% of carcinomas, while STAT5A in control normal mammary gland tissue was cytosolic.…”
Section: Stat5a/b In Tumorigenesis Of Rodent Mammary Glandmentioning
confidence: 99%